(untitled) (Global Journal of Management and Business Research, 2020)
This study goal is to highlight the likely impact of Human Resources management personalization oriented toward career management of secondary-school teachers loyalty in Cameroon This study passed through two stages Firstly an exploratory qualitative study through an interview guide This exploratory qualitative study permitted us to notice that teachers have a favorable opinion on having to choose their conditions of work in general and to list the axes of personalization customization that could be taken into account in teaching resources management After that